2011
DOI: 10.1016/j.scriptamat.2011.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth and electrical-transport properties of Ti7Si2C5 thin films synthesized by reactive sputter-deposition

Abstract: Eklund, Epitaxial growth and electrical-transport properties of Ti(7)Si(2)C(5) thin films synthesized by reactive sputter-deposition, 2011, Scripta Materialia, (65), 9, 811-814. http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In this system, there is also an intergrown phase, Ti 5 Al 2 C 3 , with alternating Ti 2 AlC-like and Ti 3 AlC 2 -like stacking [4,5,6], a type of phase known in several MAX systems [7,8,9,10], but Ti 5 Al 2 C 3 is to date the only one synthesized in bulk with full structure determination [5]. Ti 2 AlC and Ti 3 AlC 2 are promising materials for applications that demand stability at high temperatures and resistance against oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In this system, there is also an intergrown phase, Ti 5 Al 2 C 3 , with alternating Ti 2 AlC-like and Ti 3 AlC 2 -like stacking [4,5,6], a type of phase known in several MAX systems [7,8,9,10], but Ti 5 Al 2 C 3 is to date the only one synthesized in bulk with full structure determination [5]. Ti 2 AlC and Ti 3 AlC 2 are promising materials for applications that demand stability at high temperatures and resistance against oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…It follows that the c axis of a M 5 A 2 X 3 phase has to be three times the average of the M 2 AX and M 3 AX 2 c ‐axes. This description has been echoed in several other papers . A complete structure description was, however, not available until we very recently synthesized bulk samples with a high fraction of Ti 5 Al 2 C 3 which, in turn, permitted a complete structure determination .…”
mentioning
confidence: 81%
“…17,18 In 2002, the Ti 4 SiC 3 phase had been theoretically predicted, 19 and this sputtering methodology enabled the discovery of the Ti 4 SiC 3 phase as well as two intergrown phases in the form of Ti 5 Si 2 C 3 and Ti 7 Si 2 C 5 , with alternating "211" and "312" or "312" and "413" layers, respectively. 17 In 2011, Scabarozi et al showed that it is possible to deposit almost phase pure and epitaxial Ti 7 Si 2 C 5 by reactive sputtering, 20 and recently the Ti 4 SiC 3 phase has been demonstrated in bulk. [21][22][23] For industrial applications, growth from elemental sputter sources poses limitations for a simple, repeatable and scalable process, shifting the attention back to compound targets.…”
Section: Introductionmentioning
confidence: 99%